Hubungan Aktivitas Fisik Dengan Kadar Gula Darah Pasien Diabetes Mellitus Tipe II - Sari, Shela Permata; Jamil, Mokhtar; Priasmoro, Dian Pitaloka (Jurnal Keperawatan Florence Nightingale, 2025)
Diabetes is a disease that has fatal consequences for long-term health. The high prevalence of diabetes is caused by various risk factors, one of which is physical activity as part of a person's lifestyle. Physical activity plays a very important role for people with diabetes because it can convert glucose into energy and lower blood sugar levels in the body. This study was conducted to determine the relationship between physical activity and blood sugar levels in type II diabetes patients in the Mulyorejo Community Health Center area of Malang City during the period of September 2025. This study used a correlation study with a cross-sectional research design. The study population consisted of type II diabetes patients, and the sample size was 80 people using total sampling as the sampling method. Data were collected using the IPAQ questionnaire to measure physical activity and a glucometer to measure blood sugar levels. After the data was obtained, a statistical test in the form of Spearman Rank was performed. The test results obtained a p-Value of 0.0013, which is less than 0.05 as the significance value. Thus, the results of the study stated that there was a significant relationship between Physical Activity and Blood Sugar Levels in Type II DM Patients at the Mulyorejo Community Health Center in Malang City.